Protest and Democracy in West Germany - Burns, Rob. author. aut Link
X, 325 p.
Keywords: The Federal Republic of Germany has long been held up as a 'model society' on account of its economic and social policy achievements. Largely ignored, however, has been the crucial part played by extra-parliamentary protest in the maturing of democracy in that society. In this, the first comprehensive study of the subject in English, the authors trace the rich history of political protest in West Germany and examine the political role of critical intellectuals. The book will give the reader a good understanding of the crucial changes that have taken place in the political culture of the Federal Republic since the mid 1960s.